Brain and Brown Adipose Tissue Metabolism in Transgenic Tg2576 Mice Models of Alzheimer Disease Assessed Using 18F-FDG PET Imaging. (21st April 2017) - Coleman, Robert A.; Liang, Christopher; Patel, Rima; Ali, Sarah; Mukherjee, Jogeshwar
Objective: Imaging animal models of Alzheimer disease (AD) is useful for the development of therapeutic drugs and understanding AD. Transgenic Swedish hAPPswe Tg2576 mice are a good model of β-amyloid plaques. We report 18 F-fluoro-2-deoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging of brain and intrascapular brown adipose tissue (IBAT) in transgenic mice 2576 (Tg2576) and wild-type (WT) mice. Methods: Transgenic Tg2576 mice and WT mice, >18 months were injected intraperitonally with ≈ 25 to 30 MBq 18 F-FDG while awake. After 60 minutes, they were anesthetized with isoflurane (2.5%) and imaged with Inveon MicroPET. Select mice were killed, imaged ex vivo, and 20 µm sections cut for autoradiography. 18 F-FDG uptake in brain and IBAT PET and brain autoradiographs were analyzed. Results: Fasting blood glucose levels averaged 120 mg/dL for WT and 100 mg/dL for Tg2576. Compared to WT, Tg2576 mice exhibited a decrease in SUVglc in the various brain regions. Average reductions in the cerebrum regions were as high as −20%, while changes in cerebellum were −3%. Uptake of 18 F-FDG in IBAT decreased by −60% in Tg2576 mice and was found to be significant. Intrascapular brown adipose tissue findings in Tg2576 mice are new and not previously reported. Use of blood glucose for PET data analysis and corpus callosum as reference region for autoradiographic analysis were important to detect change in Tg2576 mice. Conclusion: Our results suggest that 18 F-FDG uptake in the Tg2576 mice brain show 18 F-FDG deficits only when blood glucose is taken into consideration.